Sistem Monitoring Ketinggian Air Tambak Berbasis Sms Gateway - Aurista Miftahatul Ilmah, Zakha Maisat ED, Fitrah Maharani H, Ria Dwi Izahyanti, Kukuh Widarsono (Techno Bahari, 2017)
To keep fish in the traditional ponds, the fish farmers must understand about the water circulation and pond irrigation, so that monitoring the volume of water also needs to be done because the amount of water volume in ponds became important factor in the maintenance of bandeng fish or shrimp. A water monitoring based sms gateway can help the farmers to control the pond water height from long distance without having to check periodically.